2020
DOI: 10.1039/d0ma00181c
|View full text |Cite
|
Sign up to set email alerts
|

Earth abundant colloidal carbon quantum dots for luminescent solar concentrators

Abstract: We reviewed the synthetic strategies, structure and properties of C-dots, and summarized the recent progress of C-dots based luminescent solar concentrators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 151 publications
0
34
0
Order By: Relevance
“…During last twenty years, there are many methods, which have been reported for the preparation of colloidal C-dots, [26,27] such as hydrothermal/solvothermal synthesis, [28][29][30][31][32] solid-state vacuum heating, [12] microwave-assisted synthesis, [33][34][35][36] and pyrolysis carbonization approach (Figure 1). [37 ] These wet-chemistry methods are very effective for reproducible synthesis of the colloidal C-dots, because they can control the structure and surface functional groups of the C-dots by controlling the types of precursors, reaction temperature and solvents.…”
Section: Synthesis Methods Of Qdsmentioning
confidence: 99%
See 1 more Smart Citation
“…During last twenty years, there are many methods, which have been reported for the preparation of colloidal C-dots, [26,27] such as hydrothermal/solvothermal synthesis, [28][29][30][31][32] solid-state vacuum heating, [12] microwave-assisted synthesis, [33][34][35][36] and pyrolysis carbonization approach (Figure 1). [37 ] These wet-chemistry methods are very effective for reproducible synthesis of the colloidal C-dots, because they can control the structure and surface functional groups of the C-dots by controlling the types of precursors, reaction temperature and solvents.…”
Section: Synthesis Methods Of Qdsmentioning
confidence: 99%
“…[3] Compared to inorganic quantum dots (QDs), carbon QDs (C-dots) have attracted a lot of attentions due to their unique properties, [4] such as high quantum yield, [5] good photo-and chemical-stability, [6,7] low-cost, [8,9] low-toxicity [10,11] and easy synthesis with earth-abundant precursors. [12] Because of their excellent properties, [13,14] they have been widely used as building blocks for various types of optoelectronic devices, [15] such as luminescent solar concentrators, [16,17] light emitting devices and photoelectrochemical devices. [18][19][20][21][22] For example, Wang et al studied the photocatalytic process of composite materials of C-dots and found that the electron transfer performance of C-dots cannot only improve the catalytic performance of semiconductor photocatalysts, but also improve its stability; [23] Lu et al described the upconversion photoluminescent properties of colloidal C-dots.…”
Section: Introductionmentioning
confidence: 99%
“…[65] In addition, the performance of CDs as luminescent solar concentrators has also attracted a lot of interest. [66] Reports on supramolecular immobilization of CDs on carbon nanotubes [67] and graphene oxide [68] have also demonstrated the occurrence of photoinduced electron-transfer phenomena from the 0D photoexcited CDs to the 1D CNTs and 2D graphene. Interfacing CDs with carbon nanostructures (graphene, nanotubes, etc.)…”
Section: Supramolecular Functionalization Of As-derived Cdsmentioning
confidence: 99%
“…Inorganic, shelled QD nanocrystals such as CdSe/CdS core/shell QDs and PbS/CdS core/shell QDs exhibited large Stokes shifts and high photoluminescent quantum yields (PLQYs) [58–61] . Organic QDs such as carbon quantum dots (CQDs) [62–64] and graphene quantum dots (GQDs) [65–68] are promising nanoparticles for their natural abundance, high photostability, and photoconversion capabilities. The doping of QDs with other compounds such as organic dyes such as Coumarin or metals such as Cu has resulted in improved optical efficiencies by reducing reabsorption losses and controlling the frequencies of re‐emitted light [69–75] .…”
Section: Introductionmentioning
confidence: 99%